2014
DOI: 10.1007/s10517-014-2527-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheologic Effects of Dibornol in a Model of Myocardial Ischemia/Reperfusion

Abstract: We studied the effects of novel sterically hindered phenol, 4-methyl-2,6-diisobornyl phenol (dibornol) on the rheological properties of the blood in the model of myocardial ischemia/reperfusion. Dibornol (100 mg/kg intraperitoneally for 3 days before and 5 days after ischemia/reperfusion) decreased blood viscosity by 9-25% in comparison with that in sham-operatedanimals by modulating cellular (erythrocyte deformability and aggregation) and plasma (plasma viscosity) rheological parameters. Normalization of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As shown previously, compound 1 exhibits AO properties in vitro, [18,19] surpassing the activity of BHT by a number of parameters, and is characterized by low hemolytic efficiency. [20] During the experiments on laboratory animals, compound 1 showed rheologic activity in ischemia/reperfusion [21] conditions and cardioprotective properties. [22] There have also been earlier cases of using 2,6-diisobornyl-4-methylphenol (1) in the synthesis of new derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…As shown previously, compound 1 exhibits AO properties in vitro, [18,19] surpassing the activity of BHT by a number of parameters, and is characterized by low hemolytic efficiency. [20] During the experiments on laboratory animals, compound 1 showed rheologic activity in ischemia/reperfusion [21] conditions and cardioprotective properties. [22] There have also been earlier cases of using 2,6-diisobornyl-4-methylphenol (1) in the synthesis of new derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…A series of terpenophenols was previously synthesized and its structure-activity relationship was evaluated. [23,24] It was revealed that insertion of monoterpene substituent in the phenols molecules reduces hemolytic and significant increases antioxidant activity (AOA). [25] This work is a continuation study of the synthetic potential of terpenophenols to obtain highly biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2)). The experiment revealed high antihypoxic activity of dibornol in the model of acute hypobaric hypoxia, and hemorheological activity in a model of ischemia/reperfusion [7]. When modeling incomplete cerebral ischemia with oxidative stress, a course of treatment with dibornol significantly limited the accumulation of primary and secondary products of lipid peroxidation.…”
Section: Fig 1 Shp Redox Reactions With Free Radicalsmentioning
confidence: 97%
“…Dibornol (4-methyl-2,6-diisobornylphenol) is the first drug from the group of hindered terpenophenols that proceeded to preclinical studies. It has been established that dibornol has powerful antioxidant properties, as well as hemorheological, antiplatelet and antithrombogenic types of activity [7]. The high antiradical activity is determined by the chemical formula of this compound (viz.…”
Section: Fig 1 Shp Redox Reactions With Free Radicalsmentioning
confidence: 99%